W-Band Ultra-Thin Broadband Metamaterial Absorber—Design and Applications - Jianfei Zhu; Yiwei Sheng; Li Chen; Guoliang Gao; Minchao Shi; Zhiping Yin; Jun Yang (Photonics)
This paper presents a flexible and broadband metamaterial absorber (MA) with a sandwich structure for W-band absorption. The MA uses a thin FR4 material as the dielectric layer and incorporates multiple patches of varying sizes as the top pattern layer. By optimizing the dimensions and arrangement of the metal patches, an average absorption rate exceeding 94% is achieved across the 75–110 GHz frequency range, effectively covering the entire W-band. The MA, with a thickness of only 0.22 mm and a weight less than 600 g/m2, is polarization-insensitive and maintains high absorption for TM waves within an incident angle of 45°. The structure is simple, low-cost, and compatible with PCB fabrication processes. The experimental results align well with the simulations and demonstrate effective absorbing performance in conformal applications, offering a new solution for flexible millimeter-wave absorption.